Post deposition aging of bloodstains probed by steady-state fluorescence spectroscopy - Weber, Alexis; Wójtowicz, Anna; Lednev, Igor K. (Journal of photochemistry and photobiology. B, Biology, 2021)
Blood is one of the most common body fluids discovered at crime scenes involving violent actions. It is one of the most important types of forensic evidence since it allows for the identification of the individual providing that there is a match with a known DNA profile. Determining the time since deposition (TSD) can assist investigators in establishing when the crime occurred or if a bloodstain present is actually related to the investigated event. To develop a forensically sound method for determining the TSD of a bloodstain, it is necessary to understand the underlying biochemical mechanisms occurring during aging. As biochemical processes occurring in blood are necessary for the continued survival of living organisms, they are important subjects of human biology and biomedicine and are well understood. However, the biochemistry of bloodstain aging ex vivo is primarily of interest to forensic scientists and has not yet been thoroughly researched. This preliminary study utilizes steady-state fluorescence spectroscopy to probe the changes in fluorescence properties of peripheral and menstrual blood up to 24-h post deposition. Peripheral and menstrual blood exhibited similar kinetic changes over time, assigned to the presence of the fluorophores: tryptophan, nicotinamide adenine dinucleotide (NADH), and flavins in both biological fluids. The biochemical mechanism of blood aging ex vivo is discussed. •Fluorescence of bloodstain changes significantly during 24 h post deposition.•Peripheral and menstrual bloodstains exhibit similar fluorescence characteristics.•Tryptophan, NADH and Flavins are main contributors to bloodstain fluorescence.•A biochemical mechanism of bloodstain aging is discussed.